(untitled) (Oratio Directa, 2021)
This study examines how pregnant women engaged in prostitution in Jakarta construct and interpret their lived reality. It uses a qualitative interpretive phenomenological approach based on participant observation and in-depth interviews with two participants, identified as CL and AY. The analysis draws on phenomenological reduction, noema, noesis, intentionality, and the lifeworld. The findings show that economic responsibility, limited education and employment options, family obligations, debt, and previous work experience shape the participants' decisions. Digital platforms mediate contact with clients while coded language protects privacy and reduces platform detection. Participants interpret the work primarily as a means of survival and family support rather than as a positive identity, while simultaneously managing stigma, health risks, secrecy, and unequal relations with clients and society. Their accounts reveal constrained agency: individual decisions are made within economic, gendered, and social limitations. The study is limited by its two-participant design and an inconsistency between the stated age criterion and one participant's reported age.